1998
DOI: 10.1002/(sici)1099-0518(199812)36:17<3051::aid-pola6>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of phosphorus-containing polyesters derived from 2-(6-oxido-6H-dibenz?c,e??1,2?oxaphosphorin-6-yl)-1,4- hydroxyethoxy phenylene

Abstract: A series of phosphorous‐containing aliphatic polyesters were synthesized by high‐temperature solution condensation of 2‐(6‐oxido‐6H‐dibenz〈c,e〉〈1,2〉oxaphosphorin‐6‐yl)‐1,4‐hydroxyethoxy phenylene (III) with various aromatic acid chlorides in o‐dichlorobenzene. All polyesters are amorphous and readily soluble in many organic solvents such as DMAc, NMP, DMSO, and o‐dichlorobenzene at room temperature or upon heating. These polyesters are thermally quite stable. The glass transition temperatures of these aliphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 9 publications
0
48
0
Order By: Relevance
“…DOPO-HQ-HE was prepared according to literature methods [24]. DOPO-HQ was reacted with ethylene carbonate to yield DOPO-HQ-HE (Scheme 1).…”
Section: Synthesis Of Dopo-hq-hementioning
confidence: 99%
See 1 more Smart Citation
“…DOPO-HQ-HE was prepared according to literature methods [24]. DOPO-HQ was reacted with ethylene carbonate to yield DOPO-HQ-HE (Scheme 1).…”
Section: Synthesis Of Dopo-hq-hementioning
confidence: 99%
“…The 1 H NMR peaks at 7.0-8.3 (a) ppm is assigned to aryl groups of DOPO-HQ-HE; the peaks occurring at 4.0 (b), 3.7 (c), 3.6 (d), and 2.9 (e) ppm belong to methylene groups of DOPO-HQ-HE; the peaks at 4.5 (g) and 4.8 (f) ppm are attributed to hydroxyl groups. The melting point of DOPO-HQ-HE obtained from DSC is 153-156 • C, which is the same as reported in the literature (157-158 • C) [24], which further indicates the successful synthesis of DOPO-HQ-HE.…”
Section: Synthesis Of Dopo-hq-hementioning
confidence: 99%
“…The Michael-like addition of (a) with benzoquinone is a well-known reaction applied for manufacture of a commercial flame retardant. 18,19 In a previous study we demonstrated that the replacement of an oxygen atom by a sulfur atom did not prevent the analogous Michael-like addition between (b) and benzoquinone (Scheme 3). 10 Thus, the next step of our investigation consisted of reacting compound 4 with benzoquinone.…”
Section: Resultsmentioning
confidence: 85%
“…To protect the environment and human health, researchers are focused on exploiting environmental friendly halogen‐free fire retardants for plastic materials used in various industries. Phosphorus‐containing compounds have received significant attention for many years because they are considered to be the most effective flame retardants, as demonstrated in recent studies [20–25]. Phosphorus‐containing polymers tend to char rather than burn, thus, charring provides a diffusion barrier of gaseous products to the flame, shields the polymer surface from heat and oxygen, and reduces the production of combustible gas during polymer degradation [26].…”
Section: Introductionmentioning
confidence: 99%